2013
DOI: 10.3892/mmr.2013.1500
|View full text |Cite
|
Sign up to set email alerts
|

A new selective vascular endothelial growth factor receptor 2 inhibitor ablates disease in a mouse model of psoriasis

Abstract: Psoriasis is a common chronic inflammatory skin disease and its underlying pathogenesis is still not fully understood. Therapeutic interventions are currently limited and restricted to the treatment of symptoms rather than targeting the mechanisms underlying the disease. Vascular remodeling is a hallmark of psoriasis; however, anti-vascular strategies to treat psoriasis have received little attention to date, particularly systemic treatment with a small molecule compound. The aim of this study was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…The sections were deparaffinized before staining. To demonstrate morphologic changes and eosinophil infiltration, sections were stained with hematoxylin (Merck, Darmstadt, Germany) and 1 % eosin (Sigma-Aldrich Co.) [ 21 ]. Staining with toluidine blue (Merck) was performed for mast cell detection.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were deparaffinized before staining. To demonstrate morphologic changes and eosinophil infiltration, sections were stained with hematoxylin (Merck, Darmstadt, Germany) and 1 % eosin (Sigma-Aldrich Co.) [ 21 ]. Staining with toluidine blue (Merck) was performed for mast cell detection.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF is generated in response to soluble mediators, such as cytokines, and its major receptor kinaseinsert-domain-containing receptor (KDR) which has a selective mitogenic effect on endothelial cells (43). It has been found that the epidermal over-expression of VEGF in transgenic mice, stimulated by inflammatory cytokines, leads to a phenotype nearly identical to that of PsA (44). VEGF stimulation with cytokines is therefore involved in PsA pathogenesis and several different VEGF polymorphisms are associated with an increased risk of developing PsA.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…In einer 2009 erschienen Publikation kam es unter anti-angiogener Therapie eines kolorektalen Karzinoms mit Bevacizumab, einem Antikörper gegen VEGF, auch zur Abheilung einer vorbestehenden Psoriasis (Akman et al 2009). Der therapeutische Effekt anti-angiogener Therapien konnte auch in verschiedenen Mausmodellen psoriasiformer Entzündungen belegt werden (Diaconu et al 2013;Yan et al 2013;Zibert et al 2011;Schönthaler et al 2009).…”
Section: Neben Genetischen Faktoren Spielen Verschiedene Exogene Einf...unclassified